Murray Rothbard´s Monopoly Theory applied to the Brazilian Transport Sector : An overview - Paranaiba, Adriano; Mazzoni, João Fernando Rossi (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2023)
The aim of this paper is to deploy the Austrian economic thought on monopoly to an ex-ante scenario, seeking other ways of state intervention that could create monopolies, in addition to well-known state concession. Therefore, we sought to identify regulatory costs and their indirect interference in the quantity of companies within industries, that creates a favorable scenario for the emergence of monopolies. Rothbard’s (2009) proposition about the condition of the existence of monopolies is correct, but it can be complemented with an analysis of an indirect and unintentional creation of monopolies by the State.